Dental Anomalies’ Characteristics - Sella Tunis, Tatiana (Diagnostics (Basel), 2021)
The aim of this study was to characterize dental anomalies. The pretreatment records (photographs and radiographs) of 2897 patients (41.4% males and 58.6% females) were utilized to detect dental anomalies. The dental anomalies studied were related to number, size and shape, position, and eruption. A Chi-square test was carried out to detect associations between dental anomalies, jaw, and sex. A total of 1041 (36%) of the subjects manifested at least one dental anomaly. The prevalence of all dental anomalies was jaw-dependent and greater in the maxilla, except for submerged and transmigrated teeth. The most frequently missing teeth were the maxillary lateral incisor (62.3%) and the mandibular second premolars (60.6%). The most frequent supernumerary teeth were the incisors in the maxilla (97%) and the first premolars in the mandible (43%). Dental anomalies are more frequent in the maxilla and mainly involve the anterior teeth; in the mandible, however, it is the posterior teeth. These differences can be attributed to the evolutionary history of the jaws and their diverse development patterns.